احمد ندیم قاسمی کے نعتیہ کلام میں استمداد نگاری : ایک مطالعہ: A Study of Intercession in Ahmad Nadeem Qasmi’s Naat - Batool, Itrat; Naz, Dr. Aqlima (Al-Irfan, 2024)
In Urdu literature, the tradition of writing “Naat” (poetry in praise of the Prophet Muhammad) originated from Arabic Literature. Naat as a genre is characterized by various attributes. Among the different shades of Naat, one shade is that of seeking help or "Istimdad" (Intercession). Lexically, Istimdad means seeking assistance. It refers to seeking help from some special person in times of distress, with the hope of aid. In other words, seeking help with the conviction that Allah alone is the true Helper and that others are merely means the act is known as "Istimdad." Followers of Islam, in their times of distress, seek help through the Prophet Muhammad's (SAW) intercession. This act is interpreted as Istimdad. Generally, critical study of Naat involves gaining an understanding of both the intellectual aspect of praise and the linguistic and stylistic aspects of expression. However, Istimdad is not considered fundamental to critical study of Naat and there is very little work on it. Ahmed Nadim Qasmi is a renowned poet of Urdu Naat. While his Naat poetry contains other due qualities, the aspect of Istimdad is also prominent. There isn't much relevant study on Istimdad elements in his Naat. This article is based and limits its scope to the study of Istimdad elements in Ahmed Nadim Qasmi's Naat poetry.